Economic Impact of Community Sports Coverage by Outreach Athletic Trainers on a Health System: Implications for Program Growth and Sustainability. Issue 7 (21st July 2017) - Buckner, Jeannie; Hewson, Kirstie; Barr, Michael; Woolf, Shane K.; Crawford, Thomas; Slone, Harris
Objectives: Coverage of high school and community athletics integrated within a comprehensive sports medicine program is becoming the standard of care to optimize medical treatment of athletes. While the economic benefit of clinic-based athletic trainers (AT) has been clearly demonstrated, there has been little published on the benefit of outreach AT. The purpose of the present investigation is to examine the cost-effectiveness of outreach AT for both orthopaedic providers and the health system as a whole. Methods: Review of an electronic prospective database of the outreach AT referrals to our institution was conducted for a four-year fiscal period (July 2011-June 2015). New patients as well as patients with established care at our institution were identified, and cumulative referred episodes of care and downstream revenue were recorded from billing records. New patients were defined as having no association with the hospital in the three years prior to the initial referral. All episodes of care included in this review were referred initially through the AT program; Data were recorded for the ensuing fiscal year of service. Results: Eight thousand five hundred and seventy total episodes of care resulted from 843 patients referred into the system, yielding 2, 286, 733 in total revenue (Table 1). There were 187 new patients, yielding 1602 referred episodes of care across both professional-based and hospital-based services. On average, each referred patient generated 10.17 episodes of care, with each episode generating an average of 267. Combining revenue from both professional-based and hospital-based care, an average of 2712 per patient was generated through the AT program over the four year period. Combining musculoskeletal revenue from hospital-based services and orthopaedic revenue from professional-based services yielded 761, 052 in total revenue, indicating a 33% capture rate of the total profit of the program; the remaining 66% was distributed across the health system. Conclusion: Affiliation between high school and community sports teams and orthopaedists through outreach AT is an economically sustainable, symbiotic relationship. Additionally, there is not only a positive economic impact for providers, but a distinct benefit to the entire health system. Table 1. FY12-FY15 Professional-Based and Hospital-Based Revenue. Fiscal Year Professional Hospital FY12 110, 713.97 411, 145.00 FY13 118, 670.08 354, 562.00 FY14 127, 189.86 532, 629.00 FY15 202, 282.91 429, 541.00 Total 558, 856.82 1, 727, 877.00 Total Revenue 2, 286, 733.82